Comparison of phenanthrene removal by Aspergillus niger ATC 16404 (filamentous fungi) and Pseudomonas putida KT2442 (bacteria) in enriched nutrient-liquid medium. (April 2018) - Hamzah, N; Kamil, N A F M; Singhal, N; Padhye, L; Swift, S
Abstract: Polycyclic Aromatic Hydrocarbons (PAHs) is one of the persistent and carcinogenic pollutants that needs to be eliminated from the environment. The study on degradation of PAHs by bacteria is thoroughly discussed in literature. Many strains of bacteria were chosen in order to eliminate the PAHs compound in the environment. However, there are less study on the filamentous fungi although fungi appears to be an abundant population and as dominant group in PAHs contaminated soil habitats [1], [2]. This study was conducted to determine and compare the Phenanthrene (PHE) removal by fungi and bacteria in excessive nutrient-liquid culture. Then, the survival for both strains was investigated in the presence of PHE and finally, the analysis on the fungi-PHE interaction was carried out. In condition of excessive nutrient, the removal of PHE was evaluated for fungi and bacteria in batch experiment for 5 days. PHE removal for A.niger and P.putida were found to be 97% and 20% respectively after 5 days. The presence of PHE was negatively inhibits the grow of the bacteria and the fungus. The PHE uptake mechanism for A.niger was observed to be a passive transport mechanism with 45 μg per g fungus dry weight within 24 hr of incubation. As a conclusion, filamentous fungi have the potent role in the removal of PHE as well as bacteria but depending on the strains and the condition of the environment. Fungi is known to co-metabolize the PHE meanwhile, PHE can be used as sole carbon for bacteria. This preliminary result is significant in understanding the bacteria-fungi-PHE interaction to enhance the degradation of PAHs for co-culture study in the future.